PERAN ORANG TUA TERHADAP ANAK DALAM MENUNJANG PENDIDIKAN DI DESA TOMHALU KECAMATAN TOBELO SELATAN - Yurni alita Bubala; Veronika Salem; Zoni Hengki Singal (Labor Program Studi Pendidikan Sosiologi, 2022)
The problem in this research is the role of parents who have a role in supporting the success of their children, especially in terms of increasing children's learning motivation. By using qualitative research methods with observation and interview techniques, the conclusions of this research are: The role of parents in children's education is very important, not only as breadwinners for male parents and nurturing and caring for female parents, but there are several important things that can be done. encourage children to be better in their education, namely as parents, they must understand teaching children about socio-cultural, religious, and love life as well as other factors that parents must know. And applied to children. Parents act as educators because in their work not only teach, but also train children's skills, especially training children's mental attitudes.